An Investigation of the Relationship between National Culture and Brand Loyalty – A Cross-Cultural Comparison between UK and Turkey in Luxury Fashion Online Brand Communities - Gulsun, Zeynep Seyda (2014)
Brand loyalty is accepted as one of the main indicators of brand equity which represents the overall value of the brand with its assets and liabilities. The purpose of this paper is to understand the relationship between national culture and brand loyalty since the former studies about brand loyalty have been merely carried out in Western cultures which have individualistic societies. This study endeavours to examine these aspects in luxury fashion brand communities since it is known that brand loyalty has a significant influence on customers’ preferences in luxury fashion sector. Netnographic research and qualitative interviews were conducted in UK and Turkey as these countries have significant cultural differences. The results of the research indicate that brand loyalty is influenced by different practices in different cultures. Individualistic cultures seek excitement and pleasure from their luxury shopping experience while expressing power is the key motivation for collectivist societies. In societies which have high level of power distance, customers prefer luxury brands in order to increase their social status and the key determinant of social status is seen as wealth. Service experience has a significant influence on brand loyalty for societies which have lower uncertainty avoidance due to customers’ high tendency to switch between brands. Additionally, this study demonstrated that a community pressure that have a strong impact on brand loyalty can also be seen in individualistic societies which has not been introduced before.